RESPON BEBERAPA VARIETAS KEDELAI (Glycine max L Merr) TERHADAP CEKAMAN AIR - WIYONO WIYONO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2009)
Soybean (Glycine max L Merr) varieties have different response to soil drought stress. This research aimed to assess the response of four varieties of soybean (Wilis, Anjasmoro, Local 1, and Local 2) grown in different soil water content (100%, 70% and 40% of the field capacity). The research was done from May until September 2009 at the experimental station of Agricultural Faculty of Tunas Pembangunan University using Factorial Experimental Design. The research showed that soil water stress at the level of 70% and 40% of field capacity retarded plant growth and seed yield of all soybean varieties. This shown by the decrease of plant height, dry weight of stem, dry weight of leaf, dry weight of root, root volume and all yield component and seed yield. Based on the weight of seed per plant and the number of filled pod, the Wilis variety was the most tolerant to water stress.